(untitled) (Bangladesh Journal of Zoology, 2021)
A comparative study was carried out to investigate the gastrointestinal helminth infection in domestic fowls Gallus gallus (30 specimens) and ducks Anas platyrhynchos (30 specimen). A total of 1610 helminth parasites of eight species from three taxonomic classes were recovered and identified from the different parts of alimentary canal. Among the parasitic group the cestodes were turned out to be predominant with a prevalence of 50.93% (820) whereas, the rate was 27.97% (450) and 21.19% (340) in nematodes and trematodes, respectively. The prevalence of parasites species were Ascaridia galli (80%), Echinostoma revolutum (73.33%), Raillientina echinobothrida (53.33%), Echinoparyphium recurvatum (53.33%), Cotugnia digonophora (50%), Amoebotaenia sphenoids (30%), Ascaridia hermaphoridita (43.33%) and Hymenolepis cantania (26.67%). The rate of infestation was higher (90%) in fowls than in ducks (80%) and the intensity of infections was slightly higher in ducks 31.67 (31.48 in domestic fowls). In both domestic fowls and ducks, cestode parasites were most dominant, and prevalence (83.33% and 16.80±4.31) and intensity were lower in fowls than in ducks (76.67% and 17.39 ± 4.2 2). Highest rate of infestation was observed in summer both in fowl (81.82%) and duck (70%) while, winter was associated with peak intensity of parasites in fowl (46.67) and in duck (44.28) observed in summer. The prevalence of parasites was higher in caecum of both domestic fowls and ducks. Bangladesh J. Zool. 49(1): 35-46, 2021